Pig hair fibre utilization in India: Present status and future perspectives - MOHAN, N H; NAYAK, L K; TAMULI, M K; DAS, ANUBRATA (The Indian Journal of Animal Sciences, 2014)
The hair or bristle, one of the key byproducts of pig slaughter, is used for making of brushes for domestic and industrial use. In the present review, the status of scientific knowledge on pig hair or bristle, SWOT analysis of hair sub- component of the piggery sector, balance of global trade and future prospects for promoting the effective pig hair fibre utilization by industries in India are described. The data on physical properties of pig hair or bristle remains sparse in spite of its widespread use in making different kinds of brushes in India and the world. Analysis of international trade data indicated that, India is primarily an importer of raw fibres and export accounts for less than 0.1% of the global trade. In India, most of the pig hairs/bristles are burned at the time of slaughter, wasting the valuable bio-resource permanently. On the other hand, the country imports raw fibre materials for catering the needs of domestic fibre industries. Thus, there exists abundant opportunities for promotion of pig hair fibre production and utilization in India. The advantages of promoting pig hair/bristle fibre for use in fibre industries include its superior tensile properties, availability, and environment friendliness. The industrial utilization requires detailed studies on physical and chemical characteristics of these fibres in relation with tensile properties. The efforts to promote pig fibre utilization will provide additional income to the pig farmers through better byproduct utilization, paving the way for employment generation for the rural youth through development of fibre based environment friendly industries.